Perceptions of Influencing Factors and Satisfaction With the Timing of First Childbirth Among Women of Advanced Age and Their Partners. (October 2016) - Guedes, Maryse; Canavarro, Maria Cristina
The transition to first-time parenthood at advanced maternal age has become a rising challenge for families in the 21st century. The present study aimed to examine the perceptions of influencing factors and the satisfaction with child-timing among older first-time mothers and their partners (older parents) compared with younger first-time mothers and their partners (younger parents) and to explore the relationships between these variables, depending on age group. A total of 105 older parents and 93 younger parents were recruited in a Portuguese urban referral maternity and completed self-report scales during pregnancy. Both age groups perceived that a shared desire to have children and a suitable partnership were the most influential factors. However, older parents were less satisfied with the timing of first childbirth than younger parents. Aside from some perceptions of influencing factors, advanced maternal age was the most consistent predictor of lower satisfaction with child-timing.